Sosialisasi dan Pelatihan Teknologi Padi Rakit Apung, Hidroponik Pekarangan, Pupuk Organik Cair Berbasis Mikroorganisme pada Kelompok Tani Mbuah Page dan Karang Taruna Desa Lau Solu - Nasution, Lita; Sembiring, Riduan; Simbolon, Dedi Holden; Lisnasari, Srie Faizah; Sianturi, Rivai Wulan Rejeki; Pa, Desi Adelia Br; Tarigan, Selvida Riahta Br; Yatantri, Shefia Ana (Universitas Negeri Medan, 2025)
This community service program (PKM) aimed to strengthen the capacity of two partners—the Mbuah Page Farmers’ Group and the Youth Organization of Lau Solu Village—through outreach, training, hands-on implementation, and intensive mentoring on three appropriate technologies: floating rice rafts, backyard hydroponics, and the production of liquid organic fertilizer (LOF) based on local microorganisms. The methods included open outreach sessions, stepwise practical training, technology implementation on partners’ fields/yards, and weekly monitoring over three months using pre- and post-tests. Results show increased knowledge and skills among participants; a floating-raft prototype operated on flood-prone plots, an NFT (Nutrient Film Technique) backyard hydroponics system functioned as a demonstration unit, and household-scale LOF production became routine. Early impacts were observed in more efficient input use, greater availability of quick-harvest vegetables, and strengthened organizational governance within the Youth Organization. The program concluded with a sustainability plan comprising basic production kits for three cropping cycles, farm-business management training, and assistance in drafting proposals for support from the village government/BUMDes.